Psychological Features Of Workers And Factors Affecting Them - Shohida Umarova (Euro Asian Journal Publishing, 2024)
This article discusses the possibilities of digital methods used in pedagogy today in connection with the development of the digital economy. In particular, examples of digital methods were given: "I am on the screen", "See me, hear, understand", "I am in online communication", "My online story", "From word to picture, from picture to story".
Keywords: migrant; migration; frustration; inferiority complex